A review on genotoxicity in connection to infertility and cancer. (25th August 2021) - Choudhuri, Sharmistha; Kaur, Taruneet; Jain, Sapna; Sharma, Chandresh; Asthana, Shailendra
Abstract: Genotoxicity has been identified as the main cause of infertility and a variety of cancers. The mechanisms affect the structure, quality of the information or the segregation of DNA and are not inherently correlated with mutagenicity. The concept of genotoxicity, the chemical classes that cause genetic damage and the associated mechanisms of action are discussed here. Hazardous effects of pharmaceuticals, cosmetics, agrochemicals, industrial compounds, food additives, natural toxins and nanomaterials are, in large part, identified by genotoxicity and mutagenicity tests. These are critical and early steps in industrial and regulatory health assessment. Though several in vitro experiments are commonly used and approval by regulatory agencies for commercial licensing of drugs, their accuracy in human predictions for genotoxic and mutagenic effects is frequently questioned. Treatment of real and functional genetic toxicity problems depends in detail on the knowledge of mechanisms of DNA damage in the molecular, subcellular, cellular and tissue or organ system levels. Current strategies for risk assessment of human health need revisions to achieve robust and reliable results for optimizing their effectiveness. Additionally, computerized methods, neo-biomarkers leveraging '-omics' approaches, all of which can provide a convincing genotoxicity evaluation to reduce infertility and cancer risk. Graphical abstract: Image 1 Highlights: Genotoxicity is a connection of infertility and cancers. Mechanistic understanding of DNA damage is essential for toxicity evaluation. Genotoxicity and mutagenicity predictions often challenge the accuracy of assays. An updated strategy for the risk assessment of human health is an unmet need. Neo-biomarkers may offer a reliable and improved measure to assess genotoxicity.